Child sexual abuse in focus a case study on case management in a selected local government unit in Metro Manila - Algo, Florinor F.
This thesis aims to scrutinize the case management process of a city in Metro Manila, referred to in this study as "LGU A", using the lens of child rights-based case management. The study discusses factors affecting the case management process in terms of professional, organizational, political, and cultural aspects, as evidenced in the LGU processed in handling child sexual abuse cases. The research methodology utilized an embedded case study through Rapid Assessment Instrument (RAI), In-depth Interviews, Key Informant Interviews (KII), observation and review of secondary data. Findings show that the case management process of LGU A is guided by the child rights-based protocol adopted at the policy level and published as a child protection handbook. This was patterned after the Children in Need of Special Protection Protocol on Case Management by the Department of Justice (DoJ). Observably, the actual case management process of the city is mostly affected by their confinement in organizational factors, as compared to professional, political and cultural factors. Moreover, the study found some gap at the reintegration phase in the barangay. Some Barangay Council for the Protection of Children (BCPC) are inactive; hence they lack the capacity to handle reintegrated cases. Reintegration conditions at the barangay level influence the assessments and recommendations of the LGU social workers to textend the child's stay in the institution. The LGU supports the CSA case management by using its child protection handbook, providing logistic support and fair salary among others. There is the need to improve the political, cultural and professional factors and address the hindrance or limitations posed by the organizational factors. The hindering factors cannot be addressed solely by this city. Stakeholders such as the DSWD, PASWI, child-focused organizations (CFOs), and academic can lend support for the CSA victim-survivors so they may claim their right to protection, justice and, access to services as right holders through proper child rights-based case management